HUBUNGAN KEPADATAN LALU LINTAS DENGAN KONSENTRASI COHB PADA MASYARAKAT BERISIKO TINGGI DI SEPANJANG JALAN NASIONAL KOTA SEMARANG - Devy Noviandhita Anggarani; Mursid Rahardjo; Nurjazuli Nurjazuli (Jurnal Kesehatan Masyarakat (Undip), 2016)
Road transportation contributes significantly to pollution in urban areas. The more crowded the existing motor vehicle, the higher the pollution levels of carbon monoxide (CO) in the air. Exposure of pollutant gases such as CO in the blood (COHb) in humans will lead to a decrease in capacity of the blood to bind oxygen. This study aims to determine the relationship and influence of traffic density with COHb concentrations in high-risk communities along the national road of Semarang. This type of research is observational research with cross sectional approach. The population in this study was a 20 point national roads and citizens who perform activities along the national road. Samples from this study is the fifth street with the number of respondents as many as 29 people using quota sampling technique. The results of the study by Spearman rank test showed that there is a connection traffic density with COHb concentrations in high-risk communities in the national road of Semarang with (p = 0.0001, r = 0.629) and with linear regression test found no effect of traffic congestion ( p = 0.0001), air co levels (p = 0.04) and age (p = 0.009) with COHb concentrations in high-risk communities. The conclusion of this study is there is a relationship and influence of traffic density with COHb concentrations in high-risk communities. Suggestions in this research should be a routine check CO levels of air in the city of Semarang and the realignment of environmentally friendly commercial district.